Imperious Temptations: Democratic Legitimacy and Indigenous Consent in Canada. Issue 1 (22nd August 2018) - Rollo, Toby
Abstract: Canadian courts and governments increasingly invoke principles of mutual consent and nation-to-nation negotiation as central to the goal of addressing colonial injustices in a democratic society. However, Canada continues to interpret its obligations according to the Crown's fiduciary obligation to merely consult and accommodate Aboriginal peoples on infringement of their rights. In this article, I argue that there are conceptual resources available within existing Canadian law and politics for reconstructing a democratic consensual resolution to the problem of Indigenous exclusion and dispossession. I demonstrate that meeting the basic threshold of mutual consent would first require Canadian institutions to abjure the imperious temptation to impose parochial standards of free, prior and informed consent. Second, the Crown would refuse to ensnare Indigenous communities in unconscionable bargains, agreements that they would not otherwise view as reasonable, fair or equitable. And finally, Canada would accept rights of jurisdiction over land rooted in vital relations of health and well-being, as well as a corollary right of refusal or veto over decisions deemed by affected parties to be unwanted. Résumé: Les tribunaux et les gouvernements canadiens invoquent de plus en plus les principes du consentement mutuel et de la négociation de nation à nation, jugés essentiels dans le but de réparer les injustices coloniales dans une société démocratique. Toutefois, le Canada continue d'interpréter ses obligations en fonction de l'obligation fiduciaire de la Couronne de simplement consulter et accommoder les peuples autochtones au sujet de la violation de leurs droits. Dans cet article, je soutiens qu'il existe dans les lois et les politiques canadiennes en vigueur des ressources conceptuelles pour réinventer une solution démocratique consensuelle au problème de l'exclusion et de la dépossession des autochtones. Je démontre qu'atteindre le seuil fondamental du consentement mutuel exigerait en tout premier lieu que les institutions canadiennes renoncent à la tentation impérieuse d'imposer des normes étriquées de consentement libre, préalable et éclairé. Deuxièmement, la Couronne refuserait de piéger les communautés autochtones dans des négociations indéfendables, des ententes qu'elles ne considéreraient pas autrement comme raisonnables, justes ou équitables. Enfin, le Canada accepterait des droits de juridiction sur des terres ancrées dans des relations vitales de santé et de bien-être, ainsi qu'un droit corollaire de refus ou de veto sur des décisions jugées indésirables par les parties concernées.